Characterization of sputum biomarkers for asthma-COPD overlap syndrome - Gao J; Iwamoto H; Koskela J; Alenius H; Hattori N; Kohno N; Laitinen T; Mazur W; Pulkkinen V (DOVE MEDICAL PRESS LTD, 2022)
Asthma-COPD overlap syndrome (ACOS) is a commonly encountered chronic airway disease. However, ACOS is still a consensus-based clinical phenotype and the underlying inflammatory mechanisms are inadequately characterized. To clarify the inflammatory mediatypical for ACOS, five biomarkers, namely interleukin (IL)-13, myeloperoxidase (MPO), neutrophil gelatinase-associated lipocalin (NGAL), chitinase-like protein (YKL-40), and IL-6, were selected. This study hypothesized that sputum biomarkers relevant for airway inflammation in asthma (IL-13), COPD (MPO, NGAL), or in both asthma and COPD (YKL-40, IL-6) could be used to differentiate ACOS from COPD and asthma. The aim of this study was to characterize the inflammatory profile and improve the recognition of ACOS. Induced sputum levels of IL-13, MPO, NGAL, YKL-40, and IL-6 were measured by enzyme-linked immunosorbent assay/Luminex assay in a Finnish discovery cohort (n=90) of nonsmokers, smokers, and patients with asthma, COPD, and ACOS and validated in a Japanese cohort (n=135). The classification accuracy of potential biomarkers was compared with area under the receiver operating characteristic curves. Only sputum NGAL levels could differentiate ACOS from asthma (P<0.001 and P<0.001) and COPD (P<0.05 and P=0.002) in the discovery and replication cohorts, respectively. Sputum NGAL levels were independently correlated with the percentage of pre-bronchodilator forced expiratory volume in 1 second predicted in multivariate analysis in the discovery and replication cohorts (P=0.001 and P=0.002, respectively). In conclusion, sputum biomarkers reflecting both airway inflammation and remodeling of the tissue show potential in differentiation between asthma, COPD, and ACOS.